ABOUT THE ESTABLISHMENT OF CHILDREN DISEASES CHAIRS IN THE XIX-TH CENTURY - G.L. Mikirtichan ("Paediatrician" Publishers LLC, 2007)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2007;6(2):162-165)